2011
DOI: 10.1016/j.fcr.2010.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity for grain nutrients contents in a core collection of finger millet (Eleusine coracana (L.) Gaertn.) germplasm

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 37 publications
6
61
1
Order By: Relevance
“…The high positive significant association between Fe and Zn densities has been reported in pearl millet (Rai et al, 2014 andGovindaraj et al, 2013), sorghum (Ashok Kumar et al, 2013 and2010), rice (Anandan et al, 2011), wheat (Velu et al, 2011 andZhang et al, 2010) and finger millet (Upadhyaya et al, 2011). As well as nonsignificant association of grain Fe and Zn densities with grain weight (Rai et al, 2012 andGupta et al, 2009).…”
Section: Relationship Among Traitsmentioning
confidence: 96%
“…The high positive significant association between Fe and Zn densities has been reported in pearl millet (Rai et al, 2014 andGovindaraj et al, 2013), sorghum (Ashok Kumar et al, 2013 and2010), rice (Anandan et al, 2011), wheat (Velu et al, 2011 andZhang et al, 2010) and finger millet (Upadhyaya et al, 2011). As well as nonsignificant association of grain Fe and Zn densities with grain weight (Rai et al, 2012 andGupta et al, 2009).…”
Section: Relationship Among Traitsmentioning
confidence: 96%
“…Calcium content varied from 162 to 487 mg/100 g with a mean value of 320.8 mg/100 g grain in 36 genotypes of finger millet (Vadivoo et al, 1998), 293–390 mg/100 g in six varieties of finger millet (Babu et al, 1987); 50–300 mg/100 g in another set of six varieties (Admassu et al, 2009). Furthermore, very high calcium content, 450 mg/100 g (Panwar et al, 2010) and 489 mg/100 g (Upadhyaya et al, 2011) has been reported in few finger millet genotypes. It has also been found that the average calcium content (329 mg/100 g grain) in white genotypes was considerably higher than the brown (296 mg/100 grain) genotypes (Seetharam, 2001).…”
Section: Plants: the Power House Of Calciummentioning
confidence: 99%
“…One of the practicality of classifying genotypes producing useful variabilities is to acquire information on the correlation between genetic diversity and eco-geographical background, which is frequently used by plant breeders for the development of well-organized genetic resource management and application strategies (Upadhyaya et al 2011). In the current study, it is obvious that there was little empirical evidence for the relationship between diversity pattern and geographical origin.…”
Section: Cluster Analysismentioning
confidence: 99%